Sistem Peringatan Dini Kebakaran Dengan Flame Sensor dan Arduino Uno R3 - Aldisa, Rima Tamara; Karel, Fhizyel Nazareta; Aldinugroho, Mohammad (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
An incident that is unpleasant to hear is that one fire or one in an office building is an omission of human error, caused by cigarette residue, due to LPG gas at home, or a short circuit of electric current that causes a fire and propagates. The level of losses and costs incurred by a fire incident is certainly very large. Fires that occur can be overcome, minimized, and the cost of losses that occur if we know the situation in advance and early on. For this purpose, an intelligent raft device is needed which makes a sound or full sound that there is a fire in the building. to us that there has been a fire in a room or in a public place early so that then designed a tool that can be easily reached and easy to use to prevent fires. Namely designing a fire warning system with a fire sensor and Arduino uno based on the Internet of Things by emitting a sound or sound like an alarm if it detects a fire or smoke near the device at a distance of 20cm to 250cm. This tool is very useful for laboratories because there are many personal computers inside. laboratory and the number of cables that occur in short circuits, the authors want to design and make this tool can be used in the laboratory The device to be built uses a flame sensor and uses a buzzer to make a sound.